2017
DOI: 10.1039/c6ra28246f
|View full text |Cite
|
Sign up to set email alerts
|

Improved electron extraction by a ZnO nanoparticle interlayer for solution-processed polymer solar cells

Abstract: Charge injection/extraction properties dictate the device characteristics of polymer solar cells. Based on a model system comprising PTB7-Th:PC 71 BM blends, we investigate solvent effects and interface properties of ZnO nanoparticles used as electron-transporting/hole blocking interlayers (ETL/HBL) to improve the solar cell performance and stability. We find that the polarity of processing solvents and thickness of ZnO nanoparticles ETL both play a crucial role in the device behavior. Under the optimal condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…1,2 Studies have demonstrated the versatility and potential capability of ZnO for a wide range of applications in photonic, photovoltaic and electronic devices, such as light-emitting diodes (LEDs), lasers, UV detectors, transistors and solar cells. [3][4][5][6][7][8][9] ZnO also exhibits interesting piezoelectric properties that permit its application as transducers and surface acoustic wave (SAW) and bulk acoustic wave (BAW) devices. 10,11 Furthermore, especially in the form of powder, ZnO can be applied to pigments, 12 photo(catalysts).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Studies have demonstrated the versatility and potential capability of ZnO for a wide range of applications in photonic, photovoltaic and electronic devices, such as light-emitting diodes (LEDs), lasers, UV detectors, transistors and solar cells. [3][4][5][6][7][8][9] ZnO also exhibits interesting piezoelectric properties that permit its application as transducers and surface acoustic wave (SAW) and bulk acoustic wave (BAW) devices. 10,11 Furthermore, especially in the form of powder, ZnO can be applied to pigments, 12 photo(catalysts).…”
Section: Introductionmentioning
confidence: 99%
“…Interface engineering has played an important role in improving the performance of solution processed bulk-heterojunction (BHJ) organic photovoltaic (OPV) devices. , Among the many different types of interface materials reported, zinc oxide (ZnO) thin-films are the most commonly used cathodic interlayers for inverted type OPVs . ZnO is a good electron transport material, has an appropriate work function for electron extraction, can be easily solution processed, and exhibits reasonable environmental stability. , The modification of ZnO surfaces with organic materials can have a positive impact on charge carrier collection and consequently improve OPV performance …”
Section: Introductionmentioning
confidence: 99%
“…The MO interlayer provides higher stability and lower ohmic contact resistance than the PEDOT:PSS equivalent in conventional PSCs. [11][12][13] As the electron transport layer (ETL) poly [(9,9-bis(30-(N,N-dimethylamino)propyl)-2,7-uorene)-alt-2,7-(9,9-dioctyl-uorene)] (PFN), 4,14,15 zinc oxide (ZnO) 16,17 and titanium oxide (TiOx) 9,10,18 are commonly used. ZnO has attracted much interest due to its high transparency, high air-stability and high electron mobility.…”
Section: Introductionmentioning
confidence: 99%